The Temporal Variation b-Value Temporal Variation of b-Value in Bengkulu Province Using the Maximum Likelihood Method (Earthquake Case Study 2012-2022) - Sari, Elmi Permata; Kusmita, Tri; Kurniawan, Widodo Budi (Jurnal Riset Fisika Indonesia, 2025)
Bengkulu Province is a region of high seismicity influenced by the complex interaction between the offshore subduction zone along the western margin of Sumatra and active strike-slip fault systems on land. This study investigates the temporal variation of earthquake b-values in Bengkulu Province during the period 2012–2022 using the Maximum Likelihood approach. The analysis focuses on temporal changes in the frequency–magnitude distribution and the evolving characteristics of regional seismicity. The results show clear temporal variations in b-values, indicating changes in the frequency–magnitude distribution of earthquakes over time. Variations in the a- and b-values reflect shifts in the seismicity characteristics within the framework of Bengkulu’s active tectonic setting, particularly the interaction between the Indo-Australian–Eurasian subduction system and onshore active faults. Overall, the results demonstrate that temporal changes in b-values represent the dynamics of regional seismicity in Bengkulu within an active subduction–fault tectonic framework.